EXPERIENCE OF FIGHTING AGAINST RADICALISM AND EXTREMISM IN NEW UZBEKISTAN (Academia Science Repository, 2023)
The article is devoted to the study of the experience of fighting against radicalism and extremism in New Uzbekistan. The essence of the state strategy, the legal framework, as well as information and propaganda, preventive and social rehabilitation activities in this direction are revealed.